2015
DOI: 10.5152/imj.2015.96977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parity, Maternal Body Mass Index, Maternal Weight Gain During Pregnancy, Stage of Labor, and Amniotic Fluid Volume on Ultrasonographic Estimation of Fetal Weight

Abstract: Objective: In this study, we investigate the effects of maternal body mass index (BMI), weight gain during pregnancy, delivery stage, amount of amniotic fluid, and amniotic membrane status on the calculation of estimated fetal weight. pregnant women who gave birth in our hospital were reviewed. From records, demographic data of patients, maternal BMI (kg/m 2 ), weight gain during pregnancy, delivery stage, amniotic fluid volume and amniotic membrane status, mode of delivery, ultrasound-estimated fetal weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The [3] and [4], observed that a greater percentage of women with high BMI had a significant increment in SBP and DBP in comparison to those who have a relatively stable BMI. According to a study, symptoms of obesity are intensified by excessive gaining of weight during pregnancy and the inability to lose weight six months after child birth.…”
Section: Introductionmentioning
confidence: 99%
“…The [3] and [4], observed that a greater percentage of women with high BMI had a significant increment in SBP and DBP in comparison to those who have a relatively stable BMI. According to a study, symptoms of obesity are intensified by excessive gaining of weight during pregnancy and the inability to lose weight six months after child birth.…”
Section: Introductionmentioning
confidence: 99%